DYNAMIC CHANGES IN THE BIODIVERSITY OF ALGAE IN BIOPONDS OF THE TREATMENT FACILITIES OF BUKHARA - Мустафаева Мамлакат Исмаловна (Bright Mind Publishing, 2025)
To understand the dynamics of phytoplankton, it is necessary to have a clear understanding of the seasonal periodicity and distribution of populations of mass algal species. Mass dominants include dominants that give a large amount and abundance of phytoplankton in a particular period. The composition of the dominant algae species in water bodies of different types located in different regions is not constant, it changes with changes in environmental factors such as temperature, sunlight, nutrients, water salinity, transparency, hydrogen ions (pH), gas content and others.